Pengaruh Penggunaan Media Digital Dalam Proses Pembelajaran Terhadap Prestasi Belajar Siswa Sekolah Menengah Kejuruan - Harefa, Johan Berkat; Zendrato, Ikhtiar M.S.; Telaumbanua, Rina N. (CV. SINAR HOWUHOWU, 2025)
In the digital era, digital media plays a crucial role in learning, especially in vocational high schools (SMK). This study analyzes the impact of digital media on students' academic performance. Using an experimental design, students were divided into an experimental group using e-learning modules, educational videos, and interactive applications, and a control group using traditional methods. Results showed significant improvement in the experimental group (30.77%) compared to the control group (14.29%). Digital media also enhanced students' learning motivation and material comprehension. Challenges such as limited technological access and digital literacy remain significant obstacles. Digital media provides a more flexible and interactive learning experience, allowing students to learn based on individual needs. Success depends on teacher training, technological infrastructure, and supportive policies. This study highlights the importance of digital media integration in producing vocational school graduates ready for a technology-driven workforce.